Analisis Standar Pendidik Dan Tenaga Kependidikan (Studi Di Sdn 3 Tamanagung Banyuwangi) - Sudarsri Lestari (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2018)
Standards of educators and education personnel are one of the eight national standards of education. Standards of educators and educational personnel are the standards governing the qualifications that must be possessed by educators and education personnel, both academic and non academic qualifications. SDN 3 Tamanagung is one of the primary schools in Kabupaten Banyuwangi which has educators and education personnel 8 people. This study aims to analyze the implementation of standard educators and education personnel at SDN 3 Tamanagung Banyuwangi. The method used in this research is qualitative method with descriptive research type. Data collection methods used were interviews, observation, and documentation. Testing the validity of data is done by using triangulation. The result of the research found that the head of SDN 3 Tamanagung has fulfilled the general qualification and special qualification. For educators, there is one teacher SDN 3 Tamanagung who do not meet the minimum qualifications, which is still educated diploma. In non academic qualification, all educators and education personnel at SDN 3 Tamanagung have fulfilled various competency fields, which are pedagogic, personality, social, and professional competence.